The cultural history of war in the twentieth century and after - Winter, Jay 1945- (Cambridge University Press, 2022)
This Element is a user's guide to the cultural history of warfare since 1914. It provides summaries of the basic questions historians have posed in what is now a truly global field of research. It is divided into three parts. The first provides an introduction to the cultural history of the state, focusing on the institutions of violence, both political and military, as well as introducing the key concept of the civilianization of war. The second part addresses civil society at war. It asks the question as to how do men and women try to make sense and attach meaning to the violence and cruelty of war. It also explores commemoration, religious life, humanitarianism, painting, cinema and the visual arts, and war literature and testimony. The third part explores the family, gender and migration in wartime, and shows how modern war continues to transform the world in which we live today